2016
DOI: 10.1080/14649357.2016.1235223
|View full text |Cite
|
Sign up to set email alerts
|

Property titles and the urban poor: from informality to displacement?

Abstract: An extensive literature opposes the provision of property titles for the residents of informal settlements. One concern is that titling leads to commodification and the market-driven displacement of the original inhabitants. Another is that it propagates the ideology of private ownership, undermines collective solidarity and demobilises social movements. This article, based on observations from Mexico City and Guadalajara, finds little evidence of displacement but highlights the importance of location. It supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…In this urban transition, largely initiated by the post-millennial national policy ("Democratic Security") by conservative former President Álvaro Uribe, "security" is being discursively mobilized as fulfilling the State's obligation to protect (Zeiderman, 2016), particularly in those urban territories where criminal actors directly challenge the State monopoly on urban violence (cf. Davis, 2010). As Zeiderman argues, securing the urban "population at risk" homes also includes protecting them against the climatic threat of heavy rainfall and subsequent landslides.…”
Section: Securing Homesmentioning
confidence: 99%
“…In this urban transition, largely initiated by the post-millennial national policy ("Democratic Security") by conservative former President Álvaro Uribe, "security" is being discursively mobilized as fulfilling the State's obligation to protect (Zeiderman, 2016), particularly in those urban territories where criminal actors directly challenge the State monopoly on urban violence (cf. Davis, 2010). As Zeiderman argues, securing the urban "population at risk" homes also includes protecting them against the climatic threat of heavy rainfall and subsequent landslides.…”
Section: Securing Homesmentioning
confidence: 99%
“…Despite residents not acknowledging this directly, their claim to justice and equality was inherently political, as inequality in cities of the global south is inherently shaped by a wide range of structural power and political forces, such as developing proper participation mechanisms to be able to shape decision-making (Lemanski, 2017). Thus, even when title was important for residents of Phka to feel recognized as other studies in the global south have shown (Varley, 2017), their ideas of justice cannot be fulfilled by only receiving title. These points were not reflected nor voiced by residents, nor the NGOs and development agencies they worked with.…”
Section: Resultsmentioning
confidence: 98%
“…Thus, 'the collective' is not supported by mainstream upgrading programs. Individual titling has been criticized for strengthening the tendency to oppose collective values to the individualism of private property, and dislocating people of informal settlements from their collective past (Varley, 2017). This has implications for social movements and resistance against urban injustices such as exclusion and dispossession.…”
Section: Debates On Land Formalizationmentioning
confidence: 99%
See 2 more Smart Citations